Fall armyworm (FAW) tolerant maize variety has lower FAW leaf damage under farmer management - Mulungu, Kelvin; Kasoma, Chapwa; Tesfaye, Amsal; Chisopo, Andrew; Marenya, Paswel (International Maize and Wheat Improvement Center, 2025)
Fall armyworm (FAW) (Spodoptera frugiperda) has become a major threat to maize production across Africa since its invasion in 2016. While chemical control remains the dominant response employed by farmers, concerns about pesticide resistance, environmental impacts, and costs have intensified interest in host plant resistance as a sustainable management strategy. This study evaluated the performance of a newly released FAW-tolerant (FAWTH) maize hybrid, under smallholder farmer management across three agroecological regions in Zambia during the 2024/2025 growing season. Farmers drawn from a larger randomized controlled trial were given the FAWTH variety and planted it alongside other non-FAWTH hybrids. Leaf damage was assessed on both the FAWTH and non-FAWTH plots from a random sample of 130 farmers, half from those who grew the FAWTH as a sole crop, and half from those intercropped it with a legume at about two months post planting using a standardized scoring approach. Results showed that the FAWTH variety has significantly lower FAW leaf damage compared to conventional varieties under farmer management conditions, with mean damage scores 28-33% lower depending on location and cropping system. The advantages of the FAWTH variety were more pronounced in the low-altitude, low-rainfall region I, moderately pronounced in medium rainfall (~800mm per annum) region II, and not observed in the high-altitude highrainfall (>1200mm/annum) region III. Intercropping with legumes provided additional but inconsistent benefits for FAW management. These findings demonstrate that host plant resistance can effectively reduce FAW damage under real farming conditions, though breeding programs should continue improving agronomic performance alongside pest tolerance to maximize farmer adoption and impact on food security.